Arsenic exposure during porcine oocyte maturation negatively affects embryonic development by triggering oxidative stress-induced mitochondrial dysfunction and apoptosis. (October 2022) - Kang, Hyo-Gu; Jeong, Pil-Soo; Kim, Min Ju; Joo, Ye Eun; Gwon, Min-Ah; Jeon, Se-Been; Song, Bong-Seok; Kim, Sun-Uk; Lee, Sanghoon; Sim, Bo-Woong
Abstract: Arsenic (AS), an environmental contaminant, is a known human carcinogen that can cause cancer of the lung, liver, and skin. Furthermore, AS induces oxidative stress and mitochondrial impairments in mammalian cells. However, limited information is available on the effect of AS exposure on oocyte maturation of porcine, whose anatomy, physiology, and metabolism are similar to those of human. Therefore, we examined the effect of AS exposure on the in vitro maturation (IVM) of porcine oocytes and the possible underlying mechanisms. Cumulus-cell enclosed oocytes were cultured with or without AS for maturation, and then were used for analyses. This study indicated that AS under a concentration of 1 μM significantly increased the abnormal expansion of cumulus cells and the number of oocytes maintained in meiotic arrest. In addition, AS exposure significantly reduced subsequent development of embryos and increased the rate of apoptosis of blastocysts following parthenogenetic activation (PA) and in vitro fertilization (IVF). Moreover, AS exposure induced oxidative stress with increased reactive oxygen species (ROS), and decreased glutathione (GSH), leading to reduced mitochondrial membrane potential, mitochondrial quantity, DNA damage, excessive autophagy activity, and early apoptosis in porcine oocytes. Taken together, the results demonstrated that AS exposure exerts several negative effects, such as meiotic defects and embryo developmental arrest by causing mitochondrial dysfunction and apoptosis via inducing oxidative stress.